2018
DOI: 10.1371/journal.pone.0191229
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a magnetic adsorbent from negatively-valued iron mud for methylene blue adsorption

Abstract: With increasing awareness of reduction of energy and CO2 footprint, more waste is considered recyclable for generating value-added products. Here we reported the negatively-valued iron mud, a waste from groundwater treatment plant, was successfully converted into magnetic adsorbent. Comparing with the conventional calcination method under the high temperature and pressure, the synthesis of the magnetic particles (MPs) by Fe2+/Fe3+ coprecipitation was conducted at environment-friendly condition using ascorbic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Due to their magnetic property, the Fe 3 O 4 solid phase can be separated easily from adsorbed liquid medium by using magnetic separation. Several synthesis methods such as the microemulsion technique [23], electrochemical synthesis [24], hydrothermal method [25], sol-gel process [26], and coprecipitation synthesis [27] exist for synthesizing magnetic Fe 3 O 4 materials. Among the abovementioned methods, the hydrothermal approach is an effective method to fabricate nanoparticle size materials within a short time [28].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their magnetic property, the Fe 3 O 4 solid phase can be separated easily from adsorbed liquid medium by using magnetic separation. Several synthesis methods such as the microemulsion technique [23], electrochemical synthesis [24], hydrothermal method [25], sol-gel process [26], and coprecipitation synthesis [27] exist for synthesizing magnetic Fe 3 O 4 materials. Among the abovementioned methods, the hydrothermal approach is an effective method to fabricate nanoparticle size materials within a short time [28].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to FeCl 3 , during erdite production, solid waste containing Fe oxides, such as goethite, hematite and magnetite, could be reduced by Na 2 S 56 . These wastes ubiquitously exist in groundwater treatment sludge 57,58 , red mud and fly ash 59 and could significantly decrease the cost of erdite production. Overall, our results demonstrate an alternative strategy for recycling Fe-containing solid waste for low-cost erdite production.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, the peaks of cancrinite, clinochlore, and morimotoite increased. Notably, new peaks at 2θ = 30.1 • and 35.4 • appeared, which belonged to an inverse spinel magnetite (JCPDS 19-0629) [19]. Those results indicated that the dissolution of muscovite occurred with the temperature increasing from 120 • C to 200 • C, followed by the reductive dissolution of andradite and hematite with ascorbic acid at a higher temperature.…”
Section: Conversion Of Red Mud Into Magnetic Adsorbentmentioning
confidence: 90%